THE EFFECT OF HAMBURGER STRATEGY ON STUDENTS’ READING COMPREHENSION OF RECOUNT TEXTS - Ismalianing Eviyuliwati; Cesar Abi Sarwan (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
ABSTRACTThe study is aimed at finding whether or not the Hamburger Strategy is effective to use in teaching reading comprehension of recount texts at the eighth-grade students of a Junior High School level called MTs. Daarul Ma’arif in Jakarta, Indonesia. The samples of the study are 43 students who are divided into two groups, the experimental class (22 students) and the controlled class (21 students). The research method used is a quantitative method which employs a quasi-experimental design. The data collection is conducted through pretests and posttests. The validity and the reliability of the tests are measured by using ANATES. Furthermore, the collected data are analyzed using SPSS version 23 to find the t-value, i.e. to know whether there is a significant difference of the mean scores of posttests of the two groups. The finding shows that the mean score of the experimental class is 77.27 and that of the control class is 70.00. The t-value is 2.892. In addition, the hypothesis testing shows that at the sig. 2-tailed, probability values (p) is 0.006, while alpha value (α) is 0.05. In other words, p < α, which indicates that Hѳ is rejected and Ha is accepted. In conclusion, the Hamburger Strategy is effective to use in teaching reading comprehension of recount texts at the 8th-grade students of MTs. Daarul Ma’arif, Jakarta, Indonesia. ABSTRAKPenelitian ini bertujuan untuk membuktikan apakah Strategi Hamburger efektif bila dipakai untuk mengajar Membaca Teks Recount pada siswa kelas 8 MTs Daarul Ma’arif Jakarta, Indonesia. Sampel penelitian ini terdiri dari 41 siswa yang terbagi dalam dua kelompok, kelompok ekperimen (22 siswa) dan kelompok kontrol (21 siswa). Penelitian ini adalah peneliatian kuantitatif dengan menggunakan desain kuasi-eksperimental. Pengumpulan data dilakukan dengan memberikan pretes dan postes. Validitas dan realibilitas tesnya diuji dengan ANATES. Setelah data terkumpul, dilakukan Uji-t melalui SPSS 23 untuk mengetahui adakah perbedaan yang signifikan pada rerata nilai postes kedua kelompok. Hasil penelitiannya menunjukkan bahwa rerata nilai postes kelompok eksperimen adalah 77,27, sedangkan kelompok kontrol mendapatkan rerata nilai postes sebesar 70,00. Nilai-t nya ditemukan 2,892. Sedangkan dalam uji hipotesa disebutkan nilai probabilitas (p) = 0,006 dan nilai alpha ((α) = 0.05. Dengan kata lain nilai p < nilai (α), yang artinya Hѳ ditolak dan Ha diterima. Kesimpulannya, Hamburger Strategi efektif digunakan dalam mengajar Membaca Teks Recount siswa MTs. Daarul Ma’arif Jakarta, Indonesia. How to Cite: Eviyuliwati., I., Sarwan, C. A.(2018). The Effect of Hamburger Strategy on Students’ Reading Comprehension of Recount Texts. IJEE (Indonesian Journal of English Education), 5(1), 49-60. doi:10.15408/ijee.v5i1.9880